2013
DOI: 10.1371/journal.pone.0069189
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Treasure Troves: Complete Genome Sequencing of Herbarium and Insect Museum Specimens

Abstract: Unlocking the vast genomic diversity stored in natural history collections would create unprecedented opportunities for genome-scale evolutionary, phylogenetic, domestication and population genomic studies. Many researchers have been discouraged from using historical specimens in molecular studies because of both generally limited success of DNA extraction and the challenges associated with PCR-amplifying highly degraded DNA. In today's next-generation sequencing (NGS) world, opportunities and prospects for hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
229
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(243 citation statements)
references
References 51 publications
8
229
0
2
Order By: Relevance
“…Most paleogenomic studies to date have focused on large vertebrates that inhabit cold or temperate areas or the close relatives of crop plants that have abundant genomic information available (Allaby et al, 2015;JaenickeDespres et al, 2003), although genome-scale sequencing approaches of herbarium material are increasingly being applied (Bakker et al, 2015;Beck and Semple, 2015;Besnard et al, 2014;Staats et al, 2013;Zedane et al, 2015). The ability to sequence herbarium specimens, which may represent the only samples available for rare, endangered, or extinct taxa, provides great promise towards understanding important issues from biogeographic history to domestication, taxonomy, and conservation.…”
Section: Sequencing Chloroplast Genomes From Extinct and Ancient Planmentioning
confidence: 99%
See 3 more Smart Citations
“…Most paleogenomic studies to date have focused on large vertebrates that inhabit cold or temperate areas or the close relatives of crop plants that have abundant genomic information available (Allaby et al, 2015;JaenickeDespres et al, 2003), although genome-scale sequencing approaches of herbarium material are increasingly being applied (Bakker et al, 2015;Beck and Semple, 2015;Besnard et al, 2014;Staats et al, 2013;Zedane et al, 2015). The ability to sequence herbarium specimens, which may represent the only samples available for rare, endangered, or extinct taxa, provides great promise towards understanding important issues from biogeographic history to domestication, taxonomy, and conservation.…”
Section: Sequencing Chloroplast Genomes From Extinct and Ancient Planmentioning
confidence: 99%
“…DNA obtained from herbarium samples is highly degraded (Staats et al, 2011;Weiss et al, 2015). While its fragmented nature is well suited for the relatively short read lengths produced by second generation sequencing technologies (Knapp and Hofreiter, 2010;Staats et al, 2013), it can be difficult to work with. For example, it has been demonstrated that the decay rate in herbarium samples is about ten times faster than the rate in bones (Weiss et al, 2015), and that 96 -99% of endogenous DNA may be lost during long term tissue storage (Staats et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technical barriers imposed by low-quality, degraded DNAs found in poorly dried or very old specimens have in many instances been overcome by next-generation sequencing (NGS) technologies. Consequently, an additional wealth of genetic and phylogenetic data derived from NHC became available beginning in the 2000s (Wandeler & al., 2007;Millar & al., 2008;Staats & al., 2013;Andreasen & al., 2014;Buerki & Baker, 2015;Parks & al., 2015;Suchan & al., 2016;Zedane & al., 2016;Silva & al., 2017). Other novel applications applied to NHC include, but are not limited to, isotopic and other chemical element analyses (Gritcan & al., 2016;Körner & al., 2016).…”
mentioning
confidence: 99%